Spin on fastballs thrown by elite baseball pitchers - Nagami, T.; Morohoshi, J.; Higuchi, T.; Nakata, H.; Naito, S.; Kanosue, K. (Medicine & Science in Sports & Exercise, 2011)
Purpose: In this study, we analyzed the direction of the spin axis angles and the spin rate of baseballs pitched by elite collegiate and professional pitchers.